TELAAH PERKEMBANGAN TAFSIR PERIODE MODERN - Ahmad Agus Salim; Hazmi Ihkamuddin (Sekolah Tinggi Agama Islam Sadra, 2022)
The Qur'an is the Kalāmullāh which was revealed by Jibril to the Prophet Muḥammad Saw. as a guide for those who are pious, in understanding it is not enough just to translate. So, in need of special knowledge, namely the science of interpretation. The interpretation of the Qur'an always develops every era, this is proven by the many works of interpretation that have emerged from the classical to the modern period. In addition, the scholars of the Qur'an have different opinions in dividing the periodization of the development of the interpretation of the Qur'an, either in three, four, or six periodizations, like Ḥusein Al-Dhahabī, Fahd Al-Rūmi, Ṣalāh Al-Khālidī, and Rotraud Wieland. For this reason, in this simple paper, it will be specifically explained about the development of the interpretation of the modern period which includes, socio-political and religious conditions, the background of the emergence of renewal, the characteristics of interpretation, sources, methods, styles, systematic interpretation, famous commentators of the modern period, and analysis. the validity of the interpretation in that period.